The Correlation Between Anxiety Levels and Foreign Language Learning Among University Students - wang, sirui (Pacific International Journal, 2023)
Anxiety is a prevalent psychological state that significantly impacts foreign language learning. Specifically, "second/foreign language anxiety" (FLA) refers to the anxiety associated with the acquisition of a foreign language, characterized by learners’ negative emotional reactions. Foreign language acquisition encompasses a complex range of self-perceptions, beliefs, feelings, and behaviors related to language learning. Research has indicated a connection between anxiety levels among university students and their foreign language learning outcomes. This correlation provides an opportunity for further investigation into foreign language learning strategies, anxiety reduction, and improved performance.